Immunologic checkpoints in cancer therapy: focus on the programmed death-1 (PD-1) receptor pathway - Postow, Michael; Momtaz, Parisa (Pharmacogenomics and personalized medicine, 2014)
T-lymphocytes have the potential to recognize cancer antigens as foreign and therefore eliminate them. However, immune checkpoints such as cytotoxic T-lymphocyte-associated antigen (CTLA)-4 and programmed cell death (PD)-1 receptor and its ligands (PD-L1, PD-L2) suppress the activity of T-lymphocytes. Advances in the understanding of immunology and its role in cancer have led to the development of immune checkpoint inhibitors that block CTLA-4 and PD-1 and result in durable responses in patients with a wide range of cancers. PD-1 and PD-L1 inhibitors are currently in many stages of clinical investigation, and the anti-PD-1 antibody, pembrolizumab, was recently approved by the US Food and Drug Administration. Many questions remain to be answered, such as the optimal administration schedule, biomarkers that associate with benefit, and potential for use of PD-1 agents in combination approaches. Nonetheless, immunotherapy with PD-1 blocking antibodies is now becoming an integral part in the management of cancer.